Self-Care after Severe Injuries in Circus Artists. A Philosophical Inquiry - Andrieu, Bernard (Philosophical journal of conflict and violence, 2018)
This study is based on the self-reporting by circus artists’ concerning their injuries. We refer to the theoretical framework of emersiology and argue that circus artists may be able to soothe their distress and pain by learning through their body. We will draw further on the comparison between our therapeutic approach and the techniques of self-care introduced by Michel Foucault in his History of Sexuality.